Simulation of Fire Evacuation Induction System Using Smartphone Navigation Application - Dongmin Shin(신동민); Seongman Jeon(전성만); SungPil Lee(이성필); Byungjun Cho(조병준) (한국컴퓨터정보학회논문지, 2020)
This study is intended to verify the efficiency of the information system by using the navigation application in case of fire. In the demonstration scenario simulation, it was assumed that a fire occurred 6th floor in Korea Institute of Industrial Design Promotion located in C city, K province. Eighty juniors students from K University's department of paramedics of science participated. As a result of the experiment, the demonstration simulation using the navigation application showed that the evacuation time was faster than the case of evacuation guidance in a fire situation. The need for a fire prevention system and fire prevention awareness before and after the implementation of the demonstration scenario simulation increased the need for a fire prevention system and fire prevention awareness score after the experiment. KCI Citation Count: 0